Analisis Yuridis Pencabutan Hak Politik Terhadap Terpidana Tindak Pidana Korupsi dalam Perspektif Hak Asasi Manusia - Faisal FAISAL (KEADILAN PROGRESIF, 2018)
The corruption crime is an extraordinary crime. Corruption may be committed by public officials, political figures, businessmen and even corporations. Public official and political figures dominate the corruption crimes, so that it affects widely and very detrimental to the life of nation and state of Indonesia.In investigating, adjudicating and sentencing a corruption crime cannot be against the national and international provisions. The criminal sentencing is the jury’s authority, where one of jury’s verdict is additional sentencing for revocation of political right of the corruption crime convicted. To reduce and mitigate corruption, preventive and repressive efforts need to do. One of them is by sentencing additional sentence in the form of revocation of political right of the corruption crime convicted. The revocation of a citizen’s political right is not against the human right. The Law number 39 in 1999 concerning Human rights suggests that political right belongs to derogable right or a right that can be violated by law enforcers in order to law enforcement and for the public sense of justice.